Peningkatan Kemampuan Membaca Siswa Kelas I SD melalui Suku Kata pada Mata Pelajaran Bahasa Indonesia - Sureni Sureni; Ibnu Muthi (Lembag, 2025)
Reading ability is the main foundation in basic education, especially for grade 1 elementary school students who are in the early stages of literacy development. However, many students at this level still have difficulty reading due to learning approaches that are not in accordance with the characteristics of child development. This study aims to examine the effectiveness of the syllable method in improving the reading ability of grade 1 elementary school students in the Indonesian language subject. Using a qualitative approach with a library research method, this study analyzed various scientific sources related to early reading teaching strategies. The results of the study show that the syllable method is able to facilitate reading learning in a gradual and systematic manner, starting from letter recognition, syllable combination, word formation, to reading simple sentences. This method not only improves students' phonetic and phonological abilities, but also fosters self-confidence and interest in reading. Obstacles in implementation such as lack of teacher understanding, limited learning media, and differences in student backgrounds are challenges that need to be overcome through teacher training and the provision of adequate media. These findings provide important implications for basic education practices, especially in supporting the national literacy program through the implementation of appropriate and student-based teaching strategies.